The potential of Nypa Frutican as an energy source in Indonesia: A review - Susinggih Wijana; Hendrix Yulis Setyawan; Zhijian Wan; Mingming Zhu; Dodyk Pranowo; Ika Atsari Dewi; Mega Permata Nareswari (Advances in Food Science, Sustainable Agriculture and Agroindustrial Engineering (AFSSAAE), 2023)
Nipa (Nypa fruticans Wurmb.) belongs to the Arecaceae family, covering 30% of over 4 million ha of mangrove forest in Indonesia. The most valuable part of nipa is the fruits for food, drink, handicrafts, and medicine, leaving empty fruit bunches as waste. The empty fruit bunch waste reaches 75% of the total weight of nipa fruit, producing approximately 6 Mt/ha or over 6 million Mt in a year. Nipa empty fruit bunches (EFB) are biomass containing 27.3% lignin, 36.1% cellulose, and 21.8% hemicellulose. Due to Indonesia’s increasing nipa fruit harvesting, managing and finding a suitable solution to overcome waste issues is essential. In the present review, nipa EFB’s physical and chemical properties were found suitable as a biomass energy source. Nipa’s EFB energy recovery was potentially generated from direct combustion, pyrolysis, and briquette making. The harvesting challenge and emission from direct combustion or pyrolysis process limit the nipa utilization. Education and technology dissemination is required for the coastal communities to assist in utilizing nipa.